Plasma Modified Polycarbonate Nonwovens as Filtering Material for Liquid Aerosols - Brochocka, Agnieszka; Mian, Ilona; Majchrzycka, Katarzyna; Sielski, Jan; Tyczkowski, Jacek (Instytut Biopolimerów i Włókien Chemicznych (IBWCh) , Łódź, Polska, 2014)
The filter materials commonly used in filtration processes consist of nonwoven fabrics made by melt blowing. In order to improve filtration properties they are subjected to various modifications. This paper presents the treatment of polycarbonate nonwovens with lowpressure cold plasma generated by a 13.56 MHz RF discharge using process gases such as Ar and O2. The effectiveness of such treatment was assessed on the basis of results of the penetration of nonwovens by paraffin oil mist as well as the air flow resistance. The effects of plasma on polycarbonate nonwovens, especially on their surface morphology and chemical structure, were evaluated by electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX) and X-ray photoelectron spectroscopy (XPS). The results indicate that Ar plasma is a good tool for improving the filtration properties of polycarbonate filtering materials. According to these results, the surface roughness plays an important role in the high-efficiency filtration of liquid aerosols with a small increase in air flow resistance.
Keywords: polycarbonate nonwovens; plasma treatment; liquid aerosols; filtration